2021
DOI: 10.3390/w13192787
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Impact of Vegetation Change on Hydrological Processes in Bayin River Basin, Northwest China

Abstract: Vegetation change in arid areas may lead to the redistribution of regional water resources, which can intensify the competition between ecosystems and humans for water resources. This study aimed to accurately model the impact of vegetation change on hydrological processes in an arid endorheic river watershed undergoing revegetation, namely, the middle and lower reaches of the Bayin River basin, China. A LU-SWAT-MODFLOW model was developed by integrating dynamic hydrological response units with a coupled SWAT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The middle and lower reaches of the Bayin River are in a radial flow dissipation zone, with low river runoff volumes. It is difficult to apply the traditional parameter calibration method based on river channel runoff [44]. In this study, we deployed remote sensingbased LAI data [44], evapotranspiration (ET) data [45], spring wheat yield data [46], and point-scale groundwater level data [47] to calibrate relevant parameters of the middle and lower reaches of the Bayin River at the HRU-scale, subwatershed-scale, and point-scale, respectively, in order to accurately simulate the crop growth process and the watershed hydrological process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The middle and lower reaches of the Bayin River are in a radial flow dissipation zone, with low river runoff volumes. It is difficult to apply the traditional parameter calibration method based on river channel runoff [44]. In this study, we deployed remote sensingbased LAI data [44], evapotranspiration (ET) data [45], spring wheat yield data [46], and point-scale groundwater level data [47] to calibrate relevant parameters of the middle and lower reaches of the Bayin River at the HRU-scale, subwatershed-scale, and point-scale, respectively, in order to accurately simulate the crop growth process and the watershed hydrological process.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to apply the traditional parameter calibration method based on river channel runoff [44]. In this study, we deployed remote sensingbased LAI data [44], evapotranspiration (ET) data [45], spring wheat yield data [46], and point-scale groundwater level data [47] to calibrate relevant parameters of the middle and lower reaches of the Bayin River at the HRU-scale, subwatershed-scale, and point-scale, respectively, in order to accurately simulate the crop growth process and the watershed hydrological process. This multi-scale and multi-process model calibration approach provides a reference for the simulation of ecological-hydrological processes in regions where information is deficient.…”
Section: Discussionmentioning
confidence: 99%
“…The WRB starts in the Niaoshu Mountain, flows through Gansu, Ningxia, Shanxi, and eventually joins the Yellow River at Tongguan. The average annual natural runoff is 10.4 billion m 3 . The average annual precipitation is about 610 mm, the average annual tem-perature ranges from 7.8 to 13.5 • C, and the average annual potential evapotranspiration (PET) varies from 800 to 1200 mm [36].…”
Section: Study Area and Hydrometeorological Datamentioning
confidence: 99%
“…The global hydrologic cycle and distribution of water resources are changing on various scales due to climate change and human interference during the past decades [1][2][3]. The changes in precipitation, temperature, wind speed, humidity, and solar radiation have caused decreases in streamflow in some regions [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that nitrate-nitrogen loads in this region showed a decreasing trend. Xin et al [16] combined the dynamic hydrological response units with a coupled SWAT-MODFLOW, which can reflect actual land cover changes in the basin, to simulate the vegetation change in the Bayin River basin, an arid inland river in China. The results can assist in ensuring revegetation sustainability and rationally allocating water resources in arid areas.…”
Section: Introductionmentioning
confidence: 99%